CADANGAN ZILLMER DENGAN DISTRIBUSI PARETO DAN TINGKAT BUNGA COX-INGERSOLL-ROSS - Hasriati; Ihda Hasbiyati; Audia Kirana; Agung Prabowo (LPPM Universitas Terbuka, 2022)
This article discusses Zillmer's reserves for endowment life insurance. Zillmer reserves are a type of modification of premium reserves which are calculated using prospective reserves and the Zillmer rate. In Zillmer reserves, loading which is the difference between gross premium and net premium in the first policy year is greater than standard loading, so the purpose of this research is to find a way to make the loading smaller. To achieve this goal, this article uses the Pareto distribution and the Cox-Ingersoll-Ross (CIR) interest rate model. Based on the illustration, even though in the first policy year there was still a negative loading, however, Zillmer's reserves have been increasing from time to time since the second policy year.